Identification and management of Lynch syndrome in the Middle East and North African countries: outcome of a survey in 12 countries - Sina, Mohammad; Ghorbanoghli, Zeinab; Abedrabbo, Amal; Al-Mulla, Fahd; Sghaier, Rihab Ben; Buisine, Marie-Pierre; Cortas, George; Goshayeshi, Ladan; Hadjisavvas, Andreas; Hammoudeh, Wail; Hamoudi, Waseem; Jabari, Carol; et al. (Familial cancer, 2021)
Lynch syndrome (LS), the most common inherited form of colorectal cancer (CRC), is responsible for 3% of all cases of CRC. LS is caused by a mismatch repair gene defect and is characterized by a high risk for CRC, endometrial cancer and several other cancers. Identification of LS is of utmost importance because colonoscopic surveillance substantially improves a patient’s prognosis. Recently, a network of physicians in Middle Eastern and North African (ME/NA) countries was established to improve the identification and management of LS families. The aim of the present survey was to evaluate current healthcare for families with LS in this region.
"Published online: 24 October 2020".- S. 215
Gesehen am 15.08.2024